2017
DOI: 10.1016/j.ebiom.2016.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoproteins Amplify Cytokine-signaling in Chronic Lymphocytic Leukemia Cells

Abstract: Recent studies suggest there is a high incidence of elevated low-density lipoprotein (LDL) levels in Chronic Lymphocytic Leukemia (CLL) patients and a survival benefit from cholesterol-lowering statin drugs. The mechanisms of these observations and the kinds of patients they apply to are unclear. Using an in vitro model of the pseudofollicles where CLL cells originate, LDLs were found to increase plasma membrane cholesterol, signaling molecules such as tyrosine-phosphorylated STAT3, and activated CLL cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 52 publications
(87 reference statements)
0
54
0
Order By: Relevance
“…The therapeutic target of interest for McCaw et al (2017) in their EBioMedicine article is lipid metabolism. It has been appreciated for many years that lipids have importance in CLL progression and outcomes.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The therapeutic target of interest for McCaw et al (2017) in their EBioMedicine article is lipid metabolism. It has been appreciated for many years that lipids have importance in CLL progression and outcomes.…”
mentioning
confidence: 99%
“…Within this context, McCaw et al (2017) provide a compelling argument for the role of lipids in inducing second messenger signaling in CLL. The authors were intrigued by a recent case-control study in Canada that demonstrated that CLL patients have more dyslipidemia than age-matched controls, and that CLL patients who took HMG-CoA reductase inhibitors (“statins”) had improved survival compared to CLL patients who did not take these medications, which confirmed similar results in smaller CLL cohorts (Chae et al, 2014, Friedman et al, 2010, Mozessohn et al, 2017).…”
mentioning
confidence: 99%
See 3 more Smart Citations